Dampak Pandemi Covid-19 Terhadap Pendapatan Pelaku UMKM Kecamatan Banjarmasin Utara Tahun 2022 (Studi Kasus Warung Makan Kawasan Cendana, Kayutangi ) - Julianita, Putri; Fahrati, Eny (PPJP ULM, 2023)
The Impact of the Covid-19 Pandemic on the Income of Small and Medium Enterprises in North Banjarmasin District. This study aims to determine the effect of the COVID-19 pandemic on the number of visitor arrivals/buyers, the decline in income, and how the MSMEs of Warung Makan Cendana, North Banjarmasin District, deal with the impact—qualitative research methods with research instruments in the form of interviews and short questionnaires. The research population consisted of 35 MSME owners, and as many as 10 MSMEs were selected as samples using the Simple Random Sampling method. Data analysis used descriptive analysis and the Wilcoxon Signed Rank Test. The results showed that: 1) The COVID-19 pandemic significantly affected the number of visitors of MSME owners at the Cendana Restaurant. 2) The COVID-19 pandemic has significantly impacted the income of MSME owners at the Cendana Restaurant. 3) MSME owners overcome the impact of low income by reducing cooking ingredients, implementing a shift system so they can continue to operate, reducing the number of employees, and decreasing employee salaries.